PELATIHAN PENGELOLAAN LABORATORIUM PENDIDIKAN KIMIA BAGI GURU-GURU MGMP KIMIA BLITAR - mitarlis, Mitarlis; Herdyastuti, Nuniek (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2018)
Community Service Activities (PKM) have been carried out regarding the management of chemical education laboratories in the form of training. The training was given to teachers of Blitar Regency MGMP members. The training activities aimed to increase teachers' knowledge about the management and management of the Chemistry Education Laboratory. The implementation method started from preparation and planning, implementation and evaluation. The results of the training showed an increase in participants' understanding of the management of chemical laboratory. Training activities can be carried out well, and receive positive responses from participants. As many as 67% of participants sent a report on the implementation of laboratory management tasks as a post test in their respective schools. Related to the implementation of the evaluation of the training showed a positive response as indicated by the dominant percentage in the positive (very good and good) total answer statements between 70-90%. Judging from its total usefulness, 89% stated that training activities were very useful and beneficial.